Impact of eHealth on Medication Adherence: A Review - Cahaya, Noor; Skarayadi, Oskar (Universitas Muhammadiyah Kalimantan Timur, 2022)
Non-adherence is one of the focus areas that has been developed using eHealth. Numerous eHealth interventions were developed with the aim of improving medication adherence. The aim of this research was to describes eHealth interventions impacts on medication adherence. This study was conducted in a review. Data was obtained from Pubmed and Google Scholar. Nine studies were included in this review article. Four of the nine articles obtained showed that the eHealth intervention did not improve medication adherence, while the rest showed a positive effect on increasing medication adherence. It can be concluded that the eHealth intervention still finds various challenges in its implementation to improve medication adherence.